Laser irradiation-induced structural, microstructural and optical properties change in Bi-doped As40Se60 thin films. (2nd January 2020) - Behera, Mukta; Mishra, N. C.; Naik, R.
ABSTRACT: The laser irradiation with band gap light of thermally evaporated As40 Se55 Bi5 and As40 Se45 Bi15 thin films was found to be accompanied by structural changes which in turn changed the optical constant. The thin films under investigation were characterized by the X-ray diffraction method to study the structural change and the surface morphology was checked by field emission scanning electron microscope. The composition of the films was verified from the energy dispersive X-ray analysis. The changes in optical properties due to the influence of laser irradiation were calculated from the transmission spectrum recorded by UV–Visible spectrometer in the wavelength region 400–1200 nm. The decrease in optical band gap (photodarkening) is explained on the basis of density of state model proposed by Mott–Davis. The Raman analysis showed the Raman shift and symmetric stretching vibration of As–Se.